Impacts of management practices on bioenergy feedstock yield and economic feasibility on Conservation Reserve Program grasslands - Anderson, E. K.; Aberle, E.; Chen, C.; Egenolf, J.; Harmoney, Keith; Kakani, V. G.; Kallenbach, R.; Khanna, M.; Wang, W.; Lee, D. (My University, 2015)
Perennial grass mixtures planted on Conservation Reserve Program (CRP) land are a potential source of dedicated bioenergy feedstock. Long-term nitrogen (N) and harvest management are critical factors for maximizing biomass yield while maintaining the longevity of grass stands. A six-year farm-scale study was conducted to understand the impact of weather variability on biomass yield, determine optimal N fertilization and harvest timing management practices for sustainable biomass production, and estimate economic viability at six CRP sites in the United States. Precipitation during the growing season was a critical factor for annual biomass production across all regions, and annual biomass production was severely reduced when growing season precipitation was below 50% of average. The N rate of 112 kg ha-1 produced the highest biomass yield at each location. Harvest timing resulting in the highest biomass yield was site-specific and was a factor of predominant grass type, seasonal precipitation, and the number of harvests taken per year. The use of N fertilizer for yield enhancement unambiguously increased the cost of biomass regardless of the harvest timing for all six sites. The breakeven price of biomass at the farmgate ranged from $37 to $311 Mg-1 depending on the rate of N application, timing of harvesting, and location when foregone opportunity costs were not considered. Breakeven prices ranged from $69 to $526 Mg-1 when the loss of CRP land rental payments was included as an opportunity cost. Annual cost of the CRP to the federal government could be reduced by over 8% in the states included in this study; however, this would require the biomass price to be much higher than in the case where the landowner receives the CRP land rent. This field research demonstrated the importance of long-term, farm-scale research for accurate estimation of biomass feedstock production and economic viability from perennial grasslands. © 2016 John Wiley & Sons Ltd.
Citation: Anderson, E. K., Aberle, E., Chen, C., Egenolf, J., Harmoney, K., Kakani, V. G., . . . Lee, D. (2016). Impacts of management practices on bioenergy feedstock yield and economic feasibility on Conservation Reserve Program grasslands. GCB Bioenergy. doi:10.1111/gcbb.12328
Keywords: Biomass; Breakeven Price; Cool-Season Mixture; Harvest Management; Nitrogen Management; Opportunity Cost